Limited associations between MHC diversity and reproductive success in a bird species with biparental care - Diana Ferreira; Luis M. San‐Jose; Alexandre Roulin; Arnaud Gaigher; Luca Fumagalli (Ecology and Evolution, 2024)
Abstract The selective pressure from pathogens on individuals can have direct consequences on reproduction. Genes from the major histocompatibility complex (MHC) are central to the vertebrate adaptive immune system and pathogen resistance. In species with biparental care, each sex has distinct reproductive roles and levels of investment, and due to a trade‐off with immunity, one can expect different selective regimes acting upon the MHC of each parent. Here, we addressed whether couples combine each other's variation at MHC loci to increase their breeding success. Specifically, we used a 23‐year dataset from a barn owl population (Tyto alba) to understand how MHC class Iα and IIβ functional divergence and supertypes of each parent were associated with clutch size and fledging success. We did not detect associations between MHC diversity and supertypes with the clutch size or with the fledging success. In addition, to understand the relative contribution from the MHC of the genetic parents and the social parents, we analyzed the fledging success using only a cross‐fostered dataset. We found several associations of weak‐to‐moderate effect sizes between the father's MHC and fledging success: (i) lower MHC‐Iα divergence in the genetic father increases fledging success, which might improve paternal care during incubation, and (ii) one and two MHC‐IIβ DAB2 supertypes in the social father decrease and increase, respectively, fledging success, which may affect the paternal care after hatching. Furthermore, fledging success increased when both parents did not carry MHC‐IIβ DAB1 supertype 2, which could suggest conditional effects of this supertype. Although our study relied on a substantial dataset, we showed that the associations between MHC diversity and reproductive success remain scarce and of complex interpretation in the barn owl. Moreover, our results highlighted the need to incorporate more than one proxy of reproductive success and several MHC classes to capture more complex associations.